The MBKM Program’s Development in The Al Islam Kemuhammadiyahan Subject at The Faculty of Islamic Religion Makassar Muhammadiyah University - Ferdinan Ferdinan; Nurhidaya M; Nurul Istiqamah Abu; Nur Madinah (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This study aims to analyze the development of the Merdeka Learning Campus Merdeka (MBKM) program with the subject of Al Islam and Kemuhammadiyahan (AIK), in order to create an educated generation who master science and technology (IPTEK) and have Islamic character at the Faculty of Islamic Religion. Religion (FAI), Makassar Muhammadiyah University (Unismuh Makassar). The research method used is the research and development (R and D) method, in which researchers attempt to produce a particular product and test the effectiveness of the product. In this research, a product was developed and produced in the form of guidelines for the implementation of MBKM in Al Islam and Kemuhammadiyahan subjects. There are 10 steps carried out in development research according to Sugiyono's theory, namely (1) Potential and Problems, (2) Data Collection, (3) Product Design, (4) Design Validation, (5) Revision Design, (6) Product Trial , (7) Product Revision, (8) Trial use, (9) Product Revision, (10) Mass production. The results showed that: 1. MBKM in Al Islam and Kemuhammadiyahan subjects can be implemented well, based on the results of a survey conducted on lecturers and students, 2. MBKM in Al Islam and Kemuhammadiyahan subjects in its implementation need to prepare supporting documents first, in this is the AIK MBKM guidebook and SOP, 3. MBKM in the Al Islam and Kemuhammadiyahan program needs to be socialized in stages to all Muhammadiyah Makassar University academics and campus partners, and 4. MBKM in Al Islam and Kemuhammadiyahan subjects can be implemented in various forms of programs , namely: Internships, Thematic KKN, and Research.